Association between red blood cell distribution width-to-albumin ratio at admission and all-cause mortality in patients with acute pancreatitis based on the MIMIC-III database - Qingsong Wu; Lianyi Liao; Qingjun Deng (PLoS ONE, 2025)
Objective The association between red blood cell distribution width-to-albumin (RDW/ALB) ratio (RAR) and all-cause mortality in patients with acute pancreatitis has not been fully delineated. The purpose of this study was to investigate the impact of RAR at admission on 28-day all-cause mortality in patients with acute pancreatitis. Design This investigation was conducted as a retrospective analysis utilizing data from the Medical Information Mart for Intensive Care (MIMIC)-III database. Participants Patients with acute pancreatitis were selected from the MIMIC-III database according to predefined eligibility criteria. Outcome The outcome was the all-cause mortality rates within 28 days. Results Upon screening and excluding ineligible participants, a total of 931 patients with acute pancreatitis who met the inclusion criteria were analyzed. The overall mortality at 28 days was 11.71%. The receiver operating characteristic (ROC) analysis indicated that RAR had a moderate predictive value for all-cause mortality at 28 days, with an area under the curve (AUC) of 0.669 (95%CI, 0.617–0.720; p<0.05), and the cutoff value was 4.39. Divide the patients into a high RAR group and a low RAR group based on the cutoff value. Kaplan-Meier survival analysis demonstrated a statistically significant increase in 28-day mortality among patients in the high RAR group compared to those in the low RAR group. Multivariate analysis indicated that potassium levels, total bilirubin, blood urea nitrogen, lactate, partial thromboplastin time, neutrophil and RAR were independently associated with the 28-day mortality. Multivariate Cox regression analysis confirmed that an elevated RAR was independently associated with increased mortality at 28 day (HR, 2.72; 95% CI, 1.64–4.52; p < 0.001). Conclusions This study demonstrated that RAR at admission functioned as a significant prognostic indicator for mortality in patients with acute pancreatitis.